O USE OF AGRICULTURE 4.0 AS A PERSPECTIVE OF INCREASING PRODUCTIVITY IN THE FIELD - Silva, Juliane Maíra Pedro; Cavichioli , Fabio Alexandre (Revista Interface Tecnológica, 2020)
The evolution of information technologies in the face of agricultural production is present in the context of today. Responsible for boosting agribusiness, agriculture 4.0, which brings the same concepts and methods used in Industry 4.0, results in the connection in real time using various software devices, with the aim of improving precision processes, wide use of sensors and strategic mechanisms of agriculture, automation and agricultural robotics. The objective of this work was to address the productivity and profitability of production using agriculture 4.0, also to address the main problems related to food production, as it proposes to solve the challenges and challenges of rural producers when dealing with this new era. The use of new technologies aims to reduce costs, increase food production, rationalize the use of natural resources and quality production capacity, avoiding waste.